Gender-based Violence in Lithuania during Late-Soviet Period and Post-Soviet Transformation - Kareniauskaitė, Monika (Kriminologijos studijos, 2019)
The aim of this article is to research the concept and different definitions of gender-based violence in Lithuanian society during the late Soviet period and the first decade of Lithuanian independence. These different definitions of gender-based violence are reconstructed and presented in the different discourses of criminological knowledge and beliefs: a) the expert criminological discourse; b) the so-called discourse of the ‘well-informed citizens’; c) the so-called discourse of the ‘people from the street’. The theory of three different criminilogical discourses in Lithuanian crimininology is developed by Aleksandras Dobryninas but based on theoretical insights of Alfred Schütz. The article analyzes the third level from the perspectives‘ of the victims of gender-based violence.